2011
DOI: 10.1016/j.jpeds.2010.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Obesity, Bone Mass, and Cardiometabolic Risk Factors

Abstract: Objective To compare bone mass between overweight adolescents with and without cardiometabolic risk factors (CMR). Associations of bone mass with CMR and adiposity were also determined. Study design Overweight adolescents (aged 14–18 years) were classified in Healthy (n=55), 1CMR (n=46) or ≥2CMR (n=42). CMR were measured using standard methods and defined according to pediatric definitions of metabolic syndrome. Total body bone mass, fat mass and fat-free soft tissue mass (FFST) were measured by DXA. Viscera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 38 publications
9
84
0
3
Order By: Relevance
“…The promotion of healthy practices, such as physical activity in children, provides significant benefits, such as weight control, attenuator effects on cholesterol levels and insulin resistance, regular blood pressure, well-being, and greater predisposition to active life during adolescence. (19)(20)(21) Of the components of the metabolic syndrome, systolic blood pressure was statistically high in males (p = 0.014), corroborating other results, (22) but the prevalence increases considerably when assessing the average blood pressure of students, evidencing an increase in more than half of those who were evaluated. (23) The HDL-c was the most prevalent of the metabolic changes, followed by hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 71%
“…The promotion of healthy practices, such as physical activity in children, provides significant benefits, such as weight control, attenuator effects on cholesterol levels and insulin resistance, regular blood pressure, well-being, and greater predisposition to active life during adolescence. (19)(20)(21) Of the components of the metabolic syndrome, systolic blood pressure was statistically high in males (p = 0.014), corroborating other results, (22) but the prevalence increases considerably when assessing the average blood pressure of students, evidencing an increase in more than half of those who were evaluated. (23) The HDL-c was the most prevalent of the metabolic changes, followed by hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 71%
“…The association between abdominal body fat and bone has also been explored in prepubertal [28,29] as well as in postpubertal [30,31] adolescents, and all studies suggest a negative association. The pediatric literature is currently unable to disentangle these conflicting results; existing studies have not always included both boys and girls [15,20,23,32], taken into account known determinants of bone health such as sexual maturity, physical activity and calcium intake [6,16,20,21], and some were limited by small sample sizes [6,16,23,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been established that an increased production of proinflammatory cytokines contributes to the development of osteoporosis and osteopenia [25,26]. Studies have shown that the excessive increase in body fat is associated with decreased bone mineral density [27,28].…”
Section: Discussionmentioning
confidence: 99%